087 Paramagnetic rims are a specific biomarker in multiple sclerosis. Issue 6 (27th May 2022) - Allen, Christopher; Meaton, Isobel; Altokhis, Amjad; Clarke, Margareta; Sinnecker, Tim; Wuerfel, Jens; Evangelou, Nikos; ,
Abstract : Paramagnetic rims appear as a hypointense border around the edge of Multiple Sclerosis (MS) 4 lesions when visualised on phase sensitive imaging such as T2*, FLAIR* or SWI. They are likely due to immune cell uptake of liberated iron following the destruction of oligodendrocytes. While rarer than the central vein sign, initial reports suggest they are a specific marker of MS. However, disagreement remains with different groups reporting varying prevalence, location, persistence over time and association with expanding lesions, disease stage and disability. Eight centres in the MAGNIMS (Magnetic Resonance Imaging in Multiple Sclerosis) study group contrib- uted phase imaging of 562 people. They included patients with MS, clinically isolated syndrome, migraine, NMOSD, CNS vasculitis, small vessel ischaemia, diabetes mellitus, and cluster headache along with healthy controls. In patients with MS and clinically isolated syndrome 129 lesions with a paramagnetic rim were detected. The prevalence was 23% and 26% of patients respectively, suggesting this biomarker may be present across all MS stages. Only one paramagnetic rim lesion was found in the rest of the cohort, in a patient with diabetes mellitus, confirming its exceptionally high specificity of 99.7%. christopher.allen@nottingham.ac.uk|ABN Bursary